Molecular dynamics simulation of methane hydrate dissociation by depressurisation - Yan, KeFeng; Li, XiaoSen; Chen, ZhaoYang; Li, Bo; Xu, ChunGang (Molecular Simulation, 2013)
Methane (CH4) hydrate dissociation and the mechanism by depressurisation are investigated by molecular dynamics (MD) simulation. The hydrate decomposition processes are studied by the vacuum removal method' and the normal method. It is found that the hydrate decomposition is promoted by depressurisation. The quasi-liquid layer is formed in the hydrate surface layer. The driving force of dissociation is found to be controlled by the concentration gradient between the H2O molecules of the hydrate surface layer and the H2O molecules of the hydrate inner layer. The clathrates collapse gradually, and the hydrate decomposes layer by layer. Relative to our previous MD simulation results, this study shows that the rate of the hydrate dissociation by depressurisation is slower than that by the thermal stimulation and the inhibitor injection. This study illustrated that MD simulation can play a significant role in investigating the hydrate decomposition mechanisms.